1995
DOI: 10.1111/j.1432-1033.1995.0531m.x
|View full text |Cite
|
Sign up to set email alerts
|

Signal Recognition Particle (SRP), a Ubiquitous Initiator of Protein Translocation

Abstract: In higher eukaryotes, most secretory and membrane proteins are synthesised by ribosomes which are attached to the membrane of the rough endoplasmic reticulum (RER). This allows the proteins to be translocated across that membrane already during their synthesis. The ribosomes are directed to the RER membrane by a cytoplasmic ribonucleoprotein particle, the signal recognition particle (SRP). SRP fulfills its task by virtue of three distinguishable activities: the binding of a signal sequence which, being part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
93
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 166 publications
(242 reference statements)
0
93
0
1
Order By: Relevance
“…55,56 Crystal structures of the M domain reveal two features that are postulated to form the signal-sequence binding site: a deep, highly conserved hydrophobic groove lined with Met side-chains, and the finger loop, which may act as a lid for the cavity. 47,53 Recent cryo-EM studies on complexes of ribosome, nascent chain, and SRP show an additional electron density near the M-domain of the SRP, which has been attributed to the signal sequence in the hydrophobic groove of the M-domain.…”
Section: Signal Sequence Binding By Srpmentioning
confidence: 99%
See 1 more Smart Citation
“…55,56 Crystal structures of the M domain reveal two features that are postulated to form the signal-sequence binding site: a deep, highly conserved hydrophobic groove lined with Met side-chains, and the finger loop, which may act as a lid for the cavity. 47,53 Recent cryo-EM studies on complexes of ribosome, nascent chain, and SRP show an additional electron density near the M-domain of the SRP, which has been attributed to the signal sequence in the hydrophobic groove of the M-domain.…”
Section: Signal Sequence Binding By Srpmentioning
confidence: 99%
“…However, other evidence showed that the NG domain is required for efficient signal peptide binding. 48,55,59 Our lab studied the interaction between signal peptides and SRP by using reconstituted fragments of SRP from E. coli and synthetic signal peptides. 48 We found that specific binding of signal peptides causes a dramatic and global destabilization of the SRP protein.…”
Section: Signal Sequence Binding By Srpmentioning
confidence: 99%
“…The signal recognition particle (SRP; Walter & Blobel, 1980), like the ribosome, is a cytoplasmic ribonucleoprotein particle (RNP) of ancient evolutionary origin (Poritz et al+, 1990;Bhuiyan et al+, 2000)+ SRP has an intrinsic affinity for ribosomes (Walter et al+, 1981) and its catalytic promotion of the cotranslational mode of protein translocation across membranes is well documented (Walter & Johnson, 1994;Lütcke, 1995)+ In mammals, SRP consists of the highly base-paired 300-nt-long SRP RNA and six proteins: SRP54, SRP19, and the heterodimers SRP68/72 and SRP9/14 (Fig+ 1)+ SRP9/14 associates with the terminal sequences of SRP RNA, forming the enzymatically separable Alu domain of SRP (Gundelfinger et al+, 1983), whereas the other proteins together with the central RNA sequence form the S-domain of SRP+ High resolution crystal structures are now available for a number of SRP components: the NG-and M-domains of SRP54 (Freymann et al+, 1997;Montoya et al+, 1997;Keenan et al+, 1998;Clemons et al+, 1999) and the M-domain in complex with helix 8 of SRP RNA (Batey et al+, 2000) as well as the free helices 6 (Wild et al+, 1999) and 8 (Jovine et al+, 2000) of SRP RNA, free SRP9/14 (Birse et al+, 1997), and, most recently, the Alu domain with SRP9/14 clamping together in its concave beta-sheet the 59 and 39 domains of Alu RNA (Weichenrieder et al+, 2000)+ In electron micrographs the particle appears as a flexible, tri-segmented rod of 60 Å by 260-280 Å with the two domains distinguishable at opposite ends (Andrews et al+, 1985(Andrews et al+, , 1987+ SRP selects ribosomes displaying the N-terminal signal sequence of nascent secretory and membrane proteins that first emerges at the exit pore on the large ribosomal subunit+ The Alu domain of SRP is responsible for retarding the elongation of these proteins once their export signal sequence is bound by the S-domain of SRP and prior to engagement with the translocation machinery in the endoplasmic reticulum+ Considering the apparent length of the particle, it has been pro-posed that the Alu domain might reach the cleft between the two ribosomal subunits where the elongation factors bind (Andrews et al+, 1987;Siegel & Walter, 1988), but the Alu RNP crystal structure does not support the hypothesis that elongation arrest is caused by a mechanism of mimicry-based active competition with elongation factors (Weichenrieder et al+, 2000)+ Knowledge of the preferred orientation and the degree of flexibility of the Alu domain (and the crucial C-termi...…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian SRP has been used as a model for the extensive characterization of SRP functions+ It comprises six proteins and one RNA molecule (SRP or 7SL RNA)+ The SRP 54 protein specifically recognizes signal sequences and together with stem VIII of 7SL RNA is required for the targeting of the nascent chainribosome complex to the ER membrane (for review, see Lütcke, 1995)+ SRP54 and stem VIII of 7SL RNA represent the evolutionarily most highly conserved SRP structures and have been recognized in many organisms of all three kingdoms (for references, see Samuelsson & Zwieb, 1999)+ The 59 and 39 sequences of 7SL RNA that are homologous to the Alu family of repetitive sequences as well as two proteins, SRP9 and SRP14, constitute the Alu domain of mammalian SRP+ The Alu domain mediates a transient arrest in the elongation of nascent chains that increases the efficiency of translocation in vitro (Siegel & Walter, 1985;Thomas et al+, 1997; for a review, see Bui & Strub, 1999)+ SRP9 and SRP14 are structural homologs and members of the family of small a/b RNA-binding proteins (Birse et al+, 1997)+ Binding of SR9/14 to the Alu portion of 7SL RNA appears to induce conformational changes in the protein as well as in the RNA moieties (Janiak et al+, 1992;Bui et al+, 1997;Weichenrieder et al+, 1997)+ Such adaptive changes have been suggested to play a crucial role in the direct interaction between the Alu domain and the ribosome that affects elongation arrest (Thomas et al+, 1997)+…”
Section: Introductionmentioning
confidence: 99%